Implementation Of Authoritative Statement Of The Shafiite Madhhab In The Economic Legal Ruling In The State Of Kedah And State Of Penang - Dato' Dahaman @ Dahlan, Mohd Akram; Abdul Hamid, Solahuddin; Mohd Noor, Mohd Murshidi; Ahmad, Kamarudin (UniversityPublications.net, 2019)
The authoritative statement of the Shafi‘ite madhhab is a well-established term in the policy of fatwa in Malaysia involving various issues such as worship, marriage, crime and muamalat or economic. The objective of this study is to examine the actual position of the implementation of the authoritative statement of the Shafi‘ite madhhab policy in the determination of economic fatwas in the two states which have laid the groundwork covering the views used in the determination of the fatwas whether the authoritative statement of the Shafi‘ite madhhab, Aqwal Syafi'iyyah or the other Ahl Sunnah Wal Jamaah school of thoughts such as Hanafi, Maliki and Hanbali. Qualitative study methods are used to make economic fatwas in Kedah and Penang as samples of the study. From the economic fatwas that have been filtered out of all the fatwas published by the Mufti Department of Kedah and Penang, their implementation position was analyzed using Nvivo 11 software. The findings show that economic fatwas set based on the authoritative statement of the Shafi‘ite madhhab are very small. However, the findings also show the views of other schools, such as Hanafi, Maliki and Hanbali, have been taken into account in the determination of economic fatwa in both states. Based on these findings, it can provide input to the State Mufti of Kedah and Penang to formulate strategies in strengthening the economic fatwas that will be set in the existing policy framework for current needs